PENGARUH CURRENT RATIO DAN TOTAL ASSETS TURNOVER TERHADAP NET PROFIT MARGIN PADA PT BLUE BIRD TBK PERIODE 2014 – 2023 - Nuri Oktavia; Amthy Suraya (Journal of Research and Publication Innovation, 2025)
The aim of this research was to determine the effect of Current Ratio and Total Assets Turnover on Net Profit Margin partially, simultaneously and to test the feasibility of the regression model at PT Blue Bird Tbk for the 2014-2023 period, the research method used was quantitative analysis. The data used is secondary data, company financial data used for 2014-2023. The variables used are Current Ratio (X1) and Total Assets Turnover (X2) to Net Profit Margin (Y). Based on the results of multiple linear regression analysis, the equation Y = -20.153 + 0.011 X1 + 0.478 X2. Partial test results show that the Current Ratio has a significant value of 0.683 > 0.05 with a tcount of 0.425 < ttable 2.365, so the Current Ratio has no influence and is not significant on the Net Profit Margin. Meanwhile, the partial test results for Total Assets Turnover have a significant value of 0.002 < 0.05 with tcount of 4.841 > ttable 2.365, so Total Assets Turnover has a significant and significant influence on Net Profit Margin. The results of simultaneous hypothesis testing, Current Ratio and Total Assets Turnover, have a significant effect on Net Profit Margin with a significant value of 0.001 < 0.05, and a fcount value of 26.744 > ftable 4.74.